A PRISMA Systematic Review of Waqf Research (2019–2023): Global Trends and Methodological Insights - Al Ghafri‬‏, Zahra Ali Nasser; Bensala, Youcef; Rosele, Muhammad Ikhlas (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2025)
The global importance of waqf in mitigating economic crises has been widely acknowledged, leading to a growing number of literature reviews in the field. This research is significant as it serves as a reference for scholars in waqf studies. This review analyzes waqf literature from 2019 to 2023 using the Scopus database. Utilizing the PRISMA framework as a methodology, the study initially identified 1153 articles, reducing this to 208 after applying specific filters. The findings highlight key elements of the literature on waqf, including theoretical frameworks, regional focus, and key findings and propositions. A key finding is the geographical focus of waqf research on Malaysia and Indonesia, the prevalence of case studies as a methodology, and the direction of future research agendas towards enhancing governance practices, leveraging technology, and pursuing legal reforms. The results of this review not only demonstrate what is already known but also highlight areas that remain underexplored. Therefore, the recommendations presented are formulated based on these findings to encourage more focused and relevant further research.